CARE OF NEW BORN INFANTS ACCORDING TO THE CULTURAL PERSPECTIVE OF THE BATAK TOBA TRIBE IN HUTA BAYU RAJA DISTRICT - Sondang Sidabutar (RADJA PUBLIKA, 2022)
Newborn (neonatal) is the first 28 days of human life. At this time there is a process of adjusting the baby's body system from intra-uterine life to extra-uterine life. This is the period that needs extra attention and care because this is the period when the mortality rate is the highest. The culture of the Toba Batak tribe has certain traditions that have been applied from generation to generation until now in terms of caring for newborns. This study uses a qualitative phenomenological design which aims to find out and dig deeper about newborn care according to the cultural perspective of the Toba Batak tribe in Huta Bayu Raja District, Simalungun Regency. Data collection was carried out from January 10 2014 to March 28 2014 using purposive sampling with a sample of five participants. The data collection process was carried out by in-depth interviews using a tape recorder. The results showed that care for newborns according to the Toba Batak cultural perspective consisted of organ care, umbilical cord care, hygiene and skin care, gastrointestinal care, maintaining temperature and warming the baby's body, fulfillment of nutrition, giving immunity, and other special care, namely marempas, maresek-esek and giving small amounts (blessings). The results of this study are expected to be used as knowledge and information material for nurses in getting to know the culture of the Toba Batak tribe and planning comprehensive nursing care related to newborn care. This culture must also be filtered because there is a culture that has a negative impact on the health of the baby, and it is necessary to provide counseling related to the care of newborns.